Analysis of the participation of the refraction index change under the influence of the temperature and the thermal expansion of the sensors based on fiber bragg gratings - Wojcik, W.; Kisaia, P. (Видавництво Національного університету «Львівська політехніка», 2004)
In this article calculations concerning FBG (Fiber Bragg Gratings) parameters, designed for the temperature sensors construction, are presented. As a result of the thermal expansion of the material, in which the grating is described, the temperature influence manifests itself in grating’s dimensions change, and as a consequence in grating’s period change. The change of the reflection wavelength is a result of such behaviour. Moreover the temperature has also an influence on the refractive index change of the FBG and in consequence the change of the wavelength. In this work we have made the analysis participation of thermal expansion as well as refraction index change, which influence the reflected wavelength. Our considerations include the problem of optimization the conversion characteristic.